ELECTROCHEMICAL BEHAVIOUR OF U(V1) NITRATE IN CHLOROFORM AT A MERCURY ELECTRODE THE DEPENDENCE ON SUPPORTING ELECTROLYTE (Journal of Sciences, Islamic Republic of Iran)
The mechanistic aspects of the electrochemical reduction of U(V1) nitrate at a mercury electrode in chloroform, using three different supporting electrolytes, are described. In the presence of tetrabutylarnmonium perchlorate (TBAP) as a neutral electrolyte, UO (NO ) , reduced in two irreversible electrochemical steps to form a U(V1)-U(V) binuclear complex and U(IV), respectively. In the presence of 0.75 M piperidinium perchlorate (PP) + 0.25 M piperidine (P) as supporting electrolyte, the reduction of U0 ( NO ) occurred according to a one-electron irreversible process to U (V). The same behaviour was observed in the presence of 0.5 M tributylamrnonium perchlorate + 0.3 M tributylamine. The diffusion coefficients of U(VI) and U(VI)- U(V) binuclear complex determined by chronoamperometric measurement are 8.8 cm s and 5.37 10 cm s respectively